Hiring freeze and bankruptcy in unemployment dynamics - Pietro Garibaldi (Institute for the Study of Labor (IZA), 2006)
This paper proposes a matching model that distinguishes between job creation by existing firms and job creation by firm entrants. The paper argues that vacancy posting and job destruction on the extensive margin, i.e. from firms that enter and exit the labour market, represents a viable mechanism for understanding the cyclical properties of vacancies and unemployment. The model features both hiring freeze and bankruptcies, where the former represents a sudden shut down of vacancy posting at the firm level with labour downsizing governed by natural turnover. A bankrupt firm, conversely, shut down its vacancies and lay offs its stock of workers. Recent research in macroeconomics has shown that a calibration of the Mortensen and Pissarides matching model account for 10 percent of the cyclical variability of the vacancy unemployment ratio displayed by U.S. data. A calibration of the model that explicitly considers hiring freeze and bankruptcy can account for 20 to 35 percent of the variability displayed by the data.
Keywords: J30; 330; unemployment dynamics; matching models; Arbeitsnachfrage; Unternehmensgründung; Konkurs; Arbeitsmarkt; Arbeitslosigkeit; Wirtschaftsmodell